Applying TPU blends and composite carbon fibers to flexible electromagnetic-shielding fabrics: Long-fiber-reinforced thermoplastics technique. (November 2020) - Lin, Mei-Chen; Lin, Jia-Horng; Bao, Limin
Highlights: Study combines the thermoplastic materials and carbon fibers. The composite carbon fiber filaments can be woven. Environmentally friendly and low cost process. Improved friction resistance of carbon fibers. Use coatings to improve failure mechanism of carbon fibers. Abstract: A novel manufacturing technique called long-fiber-reinforced thermoplastic (LFT) is proposed to produce continuous flexible composite carbon fibers and fabrics. During the process, a polyester hot-melt adhesive (MPTU) is added to thermoplastic polyurethane (TPU) to form TPU blends that can improve the interfacial-bonding level. The TPU blends are extruded to enwrap carbon fibers and form an outer layer. The effects of the TPU blends on the composite are examined to determine the optimal parameters. At a TPU/MPTU ratio of 85/15 wt%, the blend exhibits good miscibility and the fiber tows show the optimal cluster effect and knot properties. Consequently, the specific strength of the optimal composite carbon fibers reaches 349.27 MPa·g −1 ·cm 3 . The resulting of composite carbon fabrics shows flexibility, and an average electromagnetic-interference shielding efficiency of 28.35 dB. Overall, this study reveals that LFT technique is an effective and novel method of developing carbon fiber-reinforced thermoplastics.